To improve the academy : (Professional & Organizational Development Network in Higher Education, 2002)
An annual publication of the Professional and Organizational Development Network in Higher Education (POD), To Improve the Academy offers a resource for improvement in higher education to faculty and instructional development staff, department chairs, faculty, deans, student services staff, chief academic officers, and educational consultants.